Imperialism in Africa: Implications for Development of West Africa - Okorn, Felix Tabi; Egbe, Boypa Oyama (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
The legacy of imperialism and neocolonialism continues to shape the socio-economic landscape of Africa, particularly in the West African sub-region. Despite achieving political independence, many African nations still grapple with the lingering effects of colonial exploitation and domination. This study delves into the implications of imperialism for the development of West Africa and explores potential strategies to counter its negative impact. Employing a qualitative research approach and drawing on secondary data sources, the analysis uncovers the intricate dynamics of neocolonial control in Africa. Economic dominance, political interference, cultural subjugation, and power imbalances are among the key mechanisms through which former colonial powers maintain influence in the region. Additionally, the role of foreign aid, multinational corporations, and international financial institutions in perpetuating neocolonial practices is examined. Despite efforts towards decolonization, West Africa has struggled to achieve genuine autonomy and self-sufficiency. Economic dependence, corruption, and stunted development persist as significant challenges hindering progress. To address these issues, the study proposes tentative strategies and solutions. Promoting fair trade practices, empowering African nations to regain control over their resources and economies, and fostering regional integration and cooperation are among the proposed strategies. Strengthening governance and institutions, along with advocating for a more equitable global economic order, are also essential steps towards sustainable development. By countering neocolonial practices and embracing strategies that prioritize self-determination and equitable growth, West Africa can overcome the legacy of imperialism and realize its full potential. Acknowledging the complexities of neocolonial dynamics is crucial for formulating effective policies and initiatives aimed at dismantling neocolonial structures and fostering sustainable development in the region.